Digital Sports Management Transformation Through the Implementation of the DEBORA Platform to Enhance the Capacity of Youth Organization Administrators in Tenggarong Seberang District - Muhammad Sukron Fauzi; Dewi Rosita; Jance J Sapulete; Ramaulvi muhammad Akhyar; Naheria Naheria (The Future of Education Journal, 2026)
This Community Service Program (PKM) aimed to enhance the organizational capacity of the Youth Organization (Karang Taruna) of Tenggarong Seberang District, Kutai Kartanegara Regency, in sports organization management through the implementation of the DEBORA (Desa Bina Olahraga) platform and to improve members' competencies in using sport science-based physical fitness assessment equipment. The partner organization faced several challenges, including manual sports administration, limited digital literacy among administrators, and the underutilization of standardized physical fitness testing instruments. The program employed a participatory approach consisting of needs assessment, socialization, training, technology implementation, mentoring, and evaluation. The DEBORA platform was utilized to facilitate the digital management of member data, attendance, activity scheduling, documentation, and reporting, while the training on physical fitness assessment equipment aimed to strengthen participants' ability to conduct objective, data-driven physical fitness measurements. The evaluation results demonstrated that administrators' proficiency in operating the DEBORA platform increased from 20% to 90%, while their competency in using physical fitness assessment equipment improved from 40% to 95%. These improvements indicate that integrating digital technology with structured training and mentoring effectively strengthens sports organization governance, enhances digital literacy, and supports more effective, measurable, and sustainable physical fitness development. The program contributes to strengthening the capacity of youth organizations while supporting the achievement of the Sustainable Development Goals (SDGs), particularly SDG 3 (Good Health and Well-being), SDG 4 (Quality Education), and SDG 11 (Sustainable Cities and Communities).